Dietary replacement of peanut vines with fermented rice straw alters growth performance, nutrient digestibility, rumen fermentation characteristics in Hu lambs - Wang, Jing; Zhang, Han; Li, Lu; Li, Yufeng; Mao, Shengyong; Yin, Yuyang (Frontiers in Veterinary Science, 2025)
Efficient utilization of agricultural by-products as alternative roughage sources is essential for sustainable ruminant production where high-quality forages are limited. This study evaluated the effects of replacing peanut vines with fermented rice straw on growth performance, nutrient digestibility, rumen fermentation, and microbial communities in growing Hu lambs. Thirty male Hu lambs (19.46 ± 1.15 kg) were randomly assigned to three groups for 56 days: CON (basal diet contained 10% peanut vines), ST50 (50% replacement of peanut vines with fermented rice straw), and ST100 (100% replacement). Compared with CON, final body weight and dry matter intake were not affected in ST50 and ST100 (p > 0.05), whereas feed conversion ratio increased in ST100 (p = 0.034). Apparent digestibility of DM, OM, CP, NDF, and ADF significantly declined in ST100 but remained unchanged in ST50 (p < 0.001). Rumen pH and NH3–N remained stable, while ST50 increased propionate (p = 0.008) and reduced valerate and the acetate-to-propionate ratio (p < 0.001 and p = 0.007). Total VFA concentration was lower in ST100 than in ST50. Rumen papillae density and surface area decreased in ST100 (p > 0.05). Sequencing of 16S rRNA indicated unchanged alpha diversity but modest separation in beta diversity, with core genera (e.g., Prevotella, Ruminococcus, Succiniclasticum) conserved. Indicator species analysis showed enrichment of Selenomonas and Succinivibrionaceae_UCG-002 in CON, whereas ST100 was characterized by fiber-associated lineages, including Anaerolineae, Family_XIII_AD3011_group, and Prevotellaceae_UCG-001/003. Correlation network analysis revealed two opposing microbial clusters: one linked to propionate and NH3-N, and the other associated with acetate, butyrate, and TVFA. In conclusion, partial (50%) replacement maintained performance and improved rumen fermentation, whereas full replacement impaired digestibility. Future work should optimize fermentation techniques and microbial strategies to enhance fiber utilization.